Fabrication of low-cost beta-type Ti–Mn alloys for biomedical applications by metal injection molding process and their mechanical properties. (June 2016) - Santos, Pedro Fernandes; Niinomi, Mitsuo; Liu, Huihong; Cho, Ken; Nakai, Masaaki; Itoh, Yoshinori; Narushima, Takayuki; Ikeda, Masahiko
Abstract: Titanium and its alloys are suitable for biomedical applications owing to their good mechanical properties and biocompatibility. Beta-type Ti–Mn alloys (8–17 mass% Mn) were fabricated by metal injection molding (MIM) as a potential low cost material for use in biomedical applications. The microstructures and mechanical properties of the alloys were evaluated. For up to 13 mass% Mn, the tensile strength (1162–938 MPa) and hardness (308–294 HV) of the MIM fabricated alloys are comparable to those of Ti–Mn alloys fabricated by cold crucible levitation melting. Ti–9Mn exhibits the best balance of ultimate tensile strength (1046 MPa) and elongation (4.7%) among the tested alloys, and has a Young's modulus of 89 GPa. The observed low elongation of the alloys is attributed to the combined effects of high oxygen content, with the presence of interconnected pores and titanium carbides, the formation of which is due to carbon pickup during the debinding process. The elongation and tensile strength of the alloys decrease with increasing Mn content. The Ti–Mn alloys show good compressive properties, with Ti–17Mn showing a compressive 0.2% proof stress of 1034 MPa, and a compressive strain of 50%. Graphical abstract: The low-cost β-type Ti–Mn alloys containing 9 to 13 mass% Mn show superior or comparable tensile and compressive properties to those of the widely used Ti–6Al–4V. Ti–Mn alloys thus show potential for applications as biomaterials Highlights: Low-cost Ti–Mn alloys were developed by using a near-net shape fabrication process. Microstructural features include pores, titanium carbides and the athermal ω phase. The alloys' mechanical behavior is greatly affected by Mn content and microstructure. Ti–Mn alloys show promising results for biomedical applications.